Nitazoxanide inhibits osteosarcoma cells growth and metastasis by suppressing AKT/mTOR and Wnt/β-catenin signaling pathways - Ye, Caihong; Wei, Mengqi; Huang, Huakun; Wang, Yuping; Zhang, Lulu; Yang, Chunmei; Huang, Yanran; Luo, Jinyong (Biological chemistry, 2022)
Osteosarcoma (OS) is the most prevalent malignant bone tumor with poor prognosis. Developing new drugs for the chemotherapy of OS has been a focal point and a major obstacle of OS treatment. Nitazoxanide (NTZ), a conventional anti-parasitic agent, has got increasingly noticed because of its favorable antitumor potential. Herein, we investigated the effect of NTZ on human OS cells and . The results obtained showed that NTZ inhibited the proliferation, migration and invasion, arrested cell cycle at G1 phase, while induced apoptosis of OS cells. Mechanistically, NTZ suppressed the activity of AKT/mTOR and Wnt/β-catenin signaling pathways of OS cells. Consistent with the results , orthotopic implantation model of 143B OS cells further confirmed that NTZ inhibited OS cells growth and lung metastasis . Notably, NTZ caused no apparent damage to normal cells/tissues. In conclusion, NTZ may inhibit tumor growth and metastasis of human OS cells through suppressing AKT/mTOR and Wnt/β-catenin signaling pathways.